2013
DOI: 10.1016/j.acap.2013.05.030
|View full text |Cite
|
Sign up to set email alerts
|

A Mixed Methods Study of Parental Vaccine Decision Making and Parent–Provider Trust

Abstract: Objective To describe parental vaccine decision making behaviors and characterize trust in physician advice among parents with varying childhood vaccination behaviors. Methods Between 2008 and 2011, a mixed methods study was conducted with parents of children aged <4 years who were members of Kaiser Permanente Colorado health plan. Seven focus groups were conducted with vaccine hesitant parents. Based on findings from the focus groups, a survey was developed, pilot tested and mailed to a stratified sample of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
132
1
7

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 147 publications
(154 citation statements)
references
References 26 publications
8
132
1
7
Order By: Relevance
“…Our results suggest that participation in a vaccination program is built over a long duration through parental education about the benefits of vaccines, the reputation of the organization in their handling previous community or school-based programs, and regular and proper communication with the parents. Our results are consistent with the findings globally and in Asia on a perceived risk of the disease, knowledge and confidence over the vaccines, and a communication channel by which parents are informed about the vaccine benefits to the children and the population in general [18][19][20].…”
Section: Discussionsupporting
confidence: 81%
“…Our results suggest that participation in a vaccination program is built over a long duration through parental education about the benefits of vaccines, the reputation of the organization in their handling previous community or school-based programs, and regular and proper communication with the parents. Our results are consistent with the findings globally and in Asia on a perceived risk of the disease, knowledge and confidence over the vaccines, and a communication channel by which parents are informed about the vaccine benefits to the children and the population in general [18][19][20].…”
Section: Discussionsupporting
confidence: 81%
“…Research has shown that parental vaccine decision-making begins prenatally. 20 Parents who refused or delayed vaccines were more likely to report thinking about vaccines before their child was born and that they constantly re-evaluate their vaccine decisions, thus making prenatal visits an important time to provide pediatric vaccine information prior to the infant's first direct contact with their pediatrician. 20 Despite more than half surveyed obstetric practices offering child health information, such as car seats, pets, and circumcisions, less than a quarter provided information regarding pediatric vaccines.…”
Section: Discussionmentioning
confidence: 99%
“…20 Parents who refused or delayed vaccines were more likely to report thinking about vaccines before their child was born and that they constantly re-evaluate their vaccine decisions, thus making prenatal visits an important time to provide pediatric vaccine information prior to the infant's first direct contact with their pediatrician. 20 Despite more than half surveyed obstetric practices offering child health information, such as car seats, pets, and circumcisions, less than a quarter provided information regarding pediatric vaccines. 21 Bundling pediatric immunization information with maternal immunization information, both as methods to protect the newborn from infection, would facilitate transfer of this information to pregnant women during their prenatal visits.…”
Section: Discussionmentioning
confidence: 99%
“…We did not assess characteristics of physicians or maternal health-related beliefs that may be associated with maternal trust for this study, but prior studies have attempted to better understand these factors. In the same cohort as the previously mentioned, Colson et al study, Smith and colleagues found that maternal ratings of [9]. Interestingly, these parents reported higher levels of trust in physicians' advice about other infant care practices including nutrition and behavior and development but still at lower levels than parents who delayed or accepted vaccinations.…”
Section: Discussionmentioning
confidence: 70%